2013
DOI: 10.1016/j.comppsych.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of night eating in obese individuals with schizophrenia and schizoaffective disorder

Abstract: The prevalence of Night Eating Syndrome (NES) in the general population is estimated to be 1.5%, however, the rates among individuals with schizophrenia and schizoaffective disorder are not yet established. This study sought to examine the frequency and correlates of NES-related behaviors in a sample of obese patients with schizophrenia. One-hundred outpatients diagnosed with schizophrenia or schizoaffective disorders completed the self-report Night Eating Questionnaire (NEQ) and were then interviewed as a fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
1
28
0
3
Order By: Relevance
“…The prevalence of NES is high among those with psychiatric disorders [5,6], particularly in those with bulimia nervosa [24], sleep disorders [22] and schizophrenia [9]. We found no relationship between these psychiatric diagnosis and NES in our psychiatric outpatient sample.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The prevalence of NES is high among those with psychiatric disorders [5,6], particularly in those with bulimia nervosa [24], sleep disorders [22] and schizophrenia [9]. We found no relationship between these psychiatric diagnosis and NES in our psychiatric outpatient sample.…”
Section: Discussionmentioning
confidence: 88%
“…Lundgren and colleagues found that 12.3% of psychiatric patients met criteria for NES [5], a rate that is significantly higher than the prevalence of NES in the general population [2] and similar to the prevalence of NES among obese samples which is 6-16% [3]. Higher prevalence of major depressive disorder [7,10,11], anxiety disorders [11], schizophrenia [6,9] and substance use disorders [5] is noted among persons with NES compared with controls. There may be a reciprocal relationship between NES and psychopathology.…”
Section: Introductıonmentioning
confidence: 79%
See 3 more Smart Citations